The deepest secret : a novel - Buckley, Carla (Carla S.) (New York : Bantam Books, 2014)
Wishing for a normal life after being diagnosed with a rare medical condition that makes him lethally sensitive to light, thirteen-year-old Tyler roams the nighttime streets to observe the neighborhood family lives he covets only to become a key witness in the disappearance of a young girl.
Keywords: Family secrets -- Fiction; Secrecy -- Fiction; Suspense fiction